Respon Peserta Didik SMA Negeri Kelas X Tentang Pemanfaatan Media Pembelajaran Geografi di Kota Samarinda - Inayah Inayah; Rahmadi Rahmadi; Yaskinul Anwar (Lembaga Pengembangan Kinerja Dosen, 2025)
Learning media is one of the learning tools that greatly influences students in the learning process and this research aims to find out students' responses regarding the learning media used in learning and to find out the use of geographic media in Samarinda City State High School. This research uses a descriptive method with a qualitative approach. The data collection techniques used are indirect and direct communication. The data collection tools used were questionnaire sheets which were distributed and filled out online, conducting interviews with educators directly or face to face, and researchers conducting observations at 3 schools, namely SMAN 3, SMAN 8 and SMAN 12 in the city of Samarinda. The sampling technique uses purposive sampling. The data analysis techniques used in this research are data reduction, data presentation and drawing conclusions. Based on the results of this research, it shows that students' responses to geography learning media obtained from 3 schools, namely SMAN 3 Samarinda with a total of 72 students, obtained an average percentage score of 83.48% with very good criteria, SMAN 8 Samarinda with a total of 83.48% of students. 69 people got an average percentage score of 77.84% with very good criteria and SMAN 12 Samarinda with a total of 70 students got an average percentage score 76.80% with very good criteria. From the results of this research, it can be seen that SMAN 3 Samarinda received the highest percentage score compared to SMAN 8 and SMAN 12 Samarinda. Utilization of geographic media from the results obtained from 3 schools, namely SMAN 3 Samarinda using LCD projector, PowerPoint, ClassPoint applications, maps, atlas and YouTube. SMAN 8 Samarinda LCD projector, PowerPoint, Google Classroom application, Google Earth application, Google Maps application, and YouTube. Meanwhile, SMAN 12 Samarinda uses LCD projector, PowerPoint, YouTube, maps, globe and quizizz applications. Using learning media in schools is very useful for students to understand and improve the geography learning process. (From the results obtained by student responses based on percentages via the percentage table, the average student response has good and very good criteria).